Advantages of Imbt Contracts In Financing The Sumatera Jalintim Project with The PPP Scheme - Hariyanto, Eri (Jurnal Anggaran dan Keuangan Negara Indonesia (AKURASI), 2025)
Due to the limited budget funds for infrastructure development, the Government is implementing various financing innovations. One of the innovations in infrastructure financing is cooperation between the government and business entities (KPBU). Along with the increasing of the Islamic financial industry, Islamic banking can contribute to KPBU financing with a sharia scheme. This article presents one of the success stories of KPBU financing from Islamic banking with the Ijarah Mumtahiya Bit Tamlik (IMBT) scheme, namely the Preservation of the Jalintim Sumatra Road. This article aims to explore advantages from the sharia-based KPBU financing model so that it can be replicated for financing other regional infrastructure development. By using qualitative research methods, the author explores the KPBU financing model with a IMBT scheme to obtain advantages from the financing model. Financing with IMBT provides several benefits for BUP. IMBT is an operational lease and off-balance sheet so it does not increase leverage. Another benefit is that the investment return installments are recorded as rental costs and principal payments are flat following the depreciation of the project value.